Sustainability Performance in Hospitality Industry: Interaction of Strategic Sustainability Management and Sat Kerthi Culture - Saputra, Komang Adi Kurniawan; Subroto, Bambang; Rahman, Aulia Fuad; Saraswati, Erwin (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
This study aims to develop a model framework to identify the determinants of factors that influence sustainable performance practices in the hospitality sector. This study uses explanatory research. The unit of analysis in this study is the hotel's general manager. Data analysis was performed by multiple linear regression. It was observed that the influence of strategic sustainability management consisting of internal and external challenges as well as sat kerthi culture adopted as sustainable tourism regulation on sustainability performance based on the triple bottom line. The results show that strategic sustainability management and local sat kerthi culture significantly affect the assessment of hotel sustainability performance. The current research model can also be applied to various types of companies in the tourism and other sectors. This study offers original insight into the concept of sustainability, sat kerthi , and sustainability performance as a local culture that focuses on the concept of sustainability. Keywords: sustainability performance, strategic sustainability management, local culture, triple bottom line, green hotel